2023
DOI: 10.1038/s41598-023-30801-x
|View full text |Cite
|
Sign up to set email alerts
|

Land-use induced soil carbon stabilization at the expense of rock derived nutrients: insights from pristine Andean soils

Abstract: Soils contain significantly more carbon than the atmosphere, hence we should understand how best to stabilize it. Unfortunately, the role of human interventions on soil organic carbon (SOC) persistence in the Anthropocene remains vague, lacking adequate sites that allow unbiased direct comparisons of pristine and human influenced soils. Here we present data from a unique study system in the High Andes that guarantees pristineness of the reference sites by physical inaccessibility through vertical cliffs. By co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…This increased structural stability of pasture soil could be attributed to its higher stable fraction of soil organic matter content [ 105 ]. In addition to the great biodiversity and root exudates in pastures, the reduced soil disturbance allows the stable SOM to be less exposed to conditions that could accelerate its decomposition, allowing it to accumulate over time [ 106 ]. The presence of grazing animals in pastures also influences the cycling of organic matter and nutrients, promoting a more balanced decomposition process and further contributing to SOM carbon stabilization [ 107 ].…”
Section: Discussionmentioning
confidence: 99%
“…This increased structural stability of pasture soil could be attributed to its higher stable fraction of soil organic matter content [ 105 ]. In addition to the great biodiversity and root exudates in pastures, the reduced soil disturbance allows the stable SOM to be less exposed to conditions that could accelerate its decomposition, allowing it to accumulate over time [ 106 ]. The presence of grazing animals in pastures also influences the cycling of organic matter and nutrients, promoting a more balanced decomposition process and further contributing to SOM carbon stabilization [ 107 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors compared two island systems, Jersey (Channel Islands) and St Mary's (Isles of Scilly), to assess how different sewage infrastructure affects nitrogen loading and demonstrated that upgrading sewer systems in the islands is necessary to reduce environmental problems. Two studies focused their attention instead on the soil 9 , 10 . Jungkunst et al highlight how the relationship between human actions and the presence of organic carbon (SOC) in soil in the Anthropocene is vague, mainly due to the lack of comparison between pristine sites and sites where human activities are present 9 .…”
mentioning
confidence: 99%
“…Two studies focused their attention instead on the soil 9 , 10 . Jungkunst et al highlight how the relationship between human actions and the presence of organic carbon (SOC) in soil in the Anthropocene is vague, mainly due to the lack of comparison between pristine sites and sites where human activities are present 9 . Thanks to their study, conducted on an intact site in the high Andes, they provide evidence that thousands of years of pastoralism have increased the persistence of carbon in the soil.…”
mentioning
confidence: 99%